2014
DOI: 10.1080/14786419.2014.989844
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the antimicrobial activity ofLactobacillus caseiBifidobacterium bifidumandBifidobacterium animalisagainst foodborne pathogenic and spoilage microorganisms

Abstract: The antimicrobial activities as well as the nature of the inhibitory compounds obtained from Lactobacillus casei, Bifidobacterium bifidum and Bifidobacterium animalis strains were assayed on foodborne pathogenic - Staphyloccoccus aureus subsp. aureus (CCUG ATCC® 25926™) and Escherichia coli (ATCC® 25922™) - and spoilage microorganisms - Pseudomonas aeruginosa (ATCC® 27853™). Test producer strains showed inhibitory effect on all indicator microorganisms in diffusion of cell-free concentrated supernatant by agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
(4 reference statements)
1
4
0
1
Order By: Relevance
“…Rodriguez et al (1997) emphasized H 2 O 2 is rapidly degraded in the MRS broth, which excludes the possibility that the antimicrobial activity demonstrated by lyophilized Lactobacilli involves H 2 O 2 , as in this study, MRS was used as the growth medium for the test producer strain and lyophilization was used to concentrate the supernatant for later resuspension. de Oliveira et al (2014) also reported similar findings for lyophilized cultures.…”
Section: Discussionsupporting
confidence: 67%
“…Rodriguez et al (1997) emphasized H 2 O 2 is rapidly degraded in the MRS broth, which excludes the possibility that the antimicrobial activity demonstrated by lyophilized Lactobacilli involves H 2 O 2 , as in this study, MRS was used as the growth medium for the test producer strain and lyophilization was used to concentrate the supernatant for later resuspension. de Oliveira et al (2014) also reported similar findings for lyophilized cultures.…”
Section: Discussionsupporting
confidence: 67%
“…The present investigation was undertaken to explore the antibacterial effect of B. coagulans B37 and B. pumilus B9 on fecal coliform, Lactobacillus , and Bacillus in rat animal model. Despite the information on the antimicrobial effect of probiotic Lactobacillus and Bifidobacterium [ 22 - 24 ], there is a dearth of knowledge on the antimicrobial effect of Bacillus spp. in animal models [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…As multi resistant bacteria rise as a problem and are a major health hazard, new reduction measurements are developed to reduce specific bacterial fractions of the intestinal microbiota in animals. Nutritional intervention steps have shown promising results to shift the microbiota towards a more desirable direction [29,30,31,32,33,34]. This may create stress for the suppressed bacteria, causing a change in their metabolic activity, including the transfer of genetic material [35,36,37].…”
Section: Introductionmentioning
confidence: 99%